The Determination of Normal Percentages of Syncytiotrophoblastic Knots in Various Regions of Placenta: Where to Count the Syncytial Knots - FİLİNTE, DENİZ (DE GRUYTER POLAND SP ZOO, 2014)
Objective: The marginal, basal and subchorial regions of the placenta are considered to be more hypoxic than other regions. Therefore, it is not recommended to determine the increase in syncytiotrophoblast knots, based on the major morphological change in placental hypoxia, from the samples taken from these regions. However, the normal count of knots at various regions of placenta is not investigated. Material and Method: In this study we have sampled morphologically and clinically normal placenta with eccentric cord insertion from various sites, either close to cord entrance or away from it (marginal, non-marginal basal, non-marginal subchorial, and nonmarginal midparanchymal). The number of knots was calculated on a total of at least 100 villi for each placental sample. The normal amount of knots in different regions and comparison between them were investigated. Twenty-eight placentas with eccentric cord insertion were sampled in the same manner. Hot spots from the above mentioned regions were counted in a total of 100 villi. Results: No significant difference was found between the dual comparison of the mean percentages of different regions (p: 0.148). The variety of hypoxia in different regions of the placenta could not be demonstrated in this study. Conclusion: It is found that there is no difference in perfusion that can be morphologically demonstrated with increase in syncytiotrophoblast knot, between different regions of placenta.
Keywords: Hypoxia; Placenta; Syncytiotrophoblast; GESTATIONAL-AGE; CHORANGIOSIS; PREECLAMPSIA; PREGNANCIES; PATHOLOGY